2014
DOI: 10.1155/2014/592510
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Cranial Nerve Palsies as the First Presentation of Sarcoidosis

Abstract: Sarcoidosis is a disease process which predominantly affects the lungs but can involve virtually any organ in the human body. Neurosarcoidosis is a rare manifestation which can present in a variety of ways. There is no single diagnostic test for sarcoidosis; hence, the diagnosis is based on combined clinical, laboratorial, and radiological grounds. We describe a rare case where a patient presented with dysphagia, hoarseness, hearing loss, and unsteadiness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…However, Bridel et al [2015] found CSF-ACE to have low specificity and sensitivity in diagnosing neurosarcoidosis, providing a cohort of 440 patients with suspected neurosarcoidosis and 9 with a confirmed diagnosis by histology. Despite the controversy regarding diagnosis, there seems to be consensus that any patient with multiple cranial neuropathies, whether they are simultaneous, or sequential as in our patients, should raise suspicion for neurosarcoidosis [Carlson et al, 2015;Loor et al, 2012;Rose et al, 2014].…”
Section: Differential Diagnosismentioning
confidence: 80%
See 3 more Smart Citations
“…However, Bridel et al [2015] found CSF-ACE to have low specificity and sensitivity in diagnosing neurosarcoidosis, providing a cohort of 440 patients with suspected neurosarcoidosis and 9 with a confirmed diagnosis by histology. Despite the controversy regarding diagnosis, there seems to be consensus that any patient with multiple cranial neuropathies, whether they are simultaneous, or sequential as in our patients, should raise suspicion for neurosarcoidosis [Carlson et al, 2015;Loor et al, 2012;Rose et al, 2014].…”
Section: Differential Diagnosismentioning
confidence: 80%
“…There is no single test to diagnose neurosarcoidosis [Carlson et al, 2015], and even laboratory evidence of systemic sarcoidosis can suggest multiple etiologies, as serum ACE can be elevated in other disorders such as TB, multiple sclerosis, and Guillain-Barré syndrome [Rose et al, 2014]. In the study by Zajicek et al [1999], elevated CSF ACE was noted in 6 of the 18 patients tested, but the authors felt that an elevated CSF ACE was only helpful if it was raised out of proportion to serum ACE.…”
Section: Differential Diagnosismentioning
confidence: 98%
See 2 more Smart Citations
“…MR enhancement and thickening of cisternal portions of the cranial nerves denotes diseases like intrinsic tumors of the nerves, infiltrative malignancies, inflammatory and infectious diseases [ Table 1 ]. [ 2 3 4 5 6 7 8 ] As can be seen from Table 1 , when the nerves are significantly thickened, neoplasms (Primary/metastatic) dominate the etiologies followed by conditions like sarcoidosis, CIDP, and at times chronic infections like syphilis, schistosomiasis, chronic meningitis.…”
Section: Discussionmentioning
confidence: 99%